Digital transport traseology based on Agisoft Metashape and unmanned aerial vehicle - A. I. Nedobitkov (Вестник СибАДИ)
Introduction. A vehicle and trace evidence analysis is one of the most requested types of examinations performed within the framework of criminal cases on road traffic accidents. The main methodical guidelines for traffic and trace evidence analyses were developed in the past century, while nowadays the fourth industrial revolution is on the rise. The industrial revolution is based on computer and information technologies, various software and hardware tools. Hence there is a vital necessity in update of the vehicle and trace evidence analysis methodology in order to conform to current-day realities.Materials and methods. Results of use of the unmanned aerial vehicle and Agisoft Metashape software are presented in the article in the context of specific road traffic accidents. It was made clear that application of this method has the following advantages: firstly, time of fixation of objects of the roadway network, vehicles and their traces on traffic ways is significantly reduced; secondly, fixation accuracy is improved; thirdly, use of the method makes it possible to establish all actual facts needed to perform analysis of the mechanism of a road traffic accident. Digital models obtained using this method could be used for 3D modeling, what offers an opportunity for more accurate determination of a mode and an angle of approach of vehicles before an accident with significant reduction of financial and time expenditures.Results. It was shown that digital models of road traffic accident sites and vehicles could be entered into the case file in general as well as into an expert’s statement in particular. Such entering will improve objectivity and believability of the conducted examination. Digital models of road traffic accident sites (digital twins) could be stored for an indefinitely long time and could contain the entire information on physical accident scene. Therefore such digital models are considered as valuable information while performing additional or repeated examinations.Conclusion. The proposed method for creating a digital model of a vehicle or a site of a traffic accident can be used in digital transport traceology.